Chestnut polysaccharide rescues the damaged spermatogenesis process of asthenozoospermia-model mice by upregulating the level of palmitic acid - Han, Baoquan; Guo, Jiachen; Zhou, Bo; Li, Chunxiao; Qiao, Tian; Hua, Lei; Jiang, Yinuo; Mai, Zihang; Yu, Shuai; Tian, Yu; Zhang, Xiaoyuan; Lu, Dongliang; et al. (Frontiers in Endocrinology, 2023)
In recent years, the quality of male semen has been decreasing, and the number of male infertilities caused by asthenozoospermia is increasing year by year, and the diagnosis and treatment of patients with asthenozoospermia are gradually receiving the attention of the whole society. Due to the unknown etiology and complex pathogenesis, there is no specific treatment for asthenozoospermia. Our previous study found that the administration of chestnut polysaccharide could alter the intestinal microbiota and thus improve the testicular microenvironment, and rescue the impaired spermatogenesis process by enhancing the expression of reproduction-related genes, but its exact metabolome-related repairment mechanism of chestnut polysaccharide is still unclear. In this study, we studied the blood metabolomic changes of busulfan-induced asthenozoospermia-model mice before and after oral administration of chestnut polysaccharide with the help of metabolome, and screened two key differential metabolites (hydrogen carbonate and palmitic acid) from the set of metabolomic changes; we then analyzed the correlation between several metabolites and between different metabolites and intestinal flora by correlation analysis, and found that palmitic acid in the blood serum of mice after oral administration of chestnut polysaccharide had different degrees of correlation with various metabolites, and palmitic acid level had a significant positive correlation with the abundance of Verrucomicrobia; finally, we verified the role of palmitic acid in rescuing the damaged spermatogenesis process by using asthenozoospermia-model mice, and screened the key target gene for palmitic acid to play the rescuing effect by integrating the analysis of multiple databases. In conclusion, this study found that chestnut polysaccharide rescued the damaged spermatogenesis in asthenozoospermia-model mice by upregulating palmitic acid level, which will provide theoretical basis and technical support for the use of chestnut polysaccharide in the treatment of asthenozoospermia.